APPLICATION OF STEAM LEARNING METHODS TO INCREASE STUDENT CREATIVITY AND INNOVATION - Opan Arifudin; Sepriadi Bumbungan; Ika Kartika (International Journal of Teaching and Learning, 2026)
This research aims to explore the application of the STEAM (Science, Technology, Engineering, Arts, and Mathematics) learning method and its impact on increasing student creativity and innovation. The literature review method was used to collect and analyze various previous studies that examined the effectiveness of the STEAM approach in education. The findings show that the STEAM method makes a significant contribution to the development of critical thinking, problem-solving, and collaborative skills. In addition, the integration of arts in STEM learning encourages students to think more creatively, generate innovative ideas, and face challenges more flexibly. This conclusion confirms that the application of the STEAM method not only enriches students' learning experiences but also prepares them to become innovative and adaptive individuals in the future. The implications of this research suggest that educational systems should adopt STEAM methods more widely to maximize students' creative and innovative potential.